A New Phenolic Compound from the Leaves of Nicotiana tabacum and its Anti-tobacco Mosaic Virus Activities - Chen, Yong-Kuan; Wu, Chun-Yan; Yang, Li-Xin; Miao, Ming-Ming; Yang, Guang-Yu; Xu, Gang (Asian Journal of Chemistry, 2014)
A new phenolic compound, 5-(4-hydroxybutyl)-2,3-dimethoxyphenol (1), was isolated from the leaves of Nicotiana tabacum. Its structure was elucidated by spectroscopic methods, including extensive 1D-NMR and 2D-NMR techniques. Compound 1 was also tested for its anti-tobacco mosaic virus (anti-TMV) activity and it showed high anti-TMV activity with inhibition rate of 22.2 %.